Ecologia reprodutiva de duas espécies de Leptodactylus e a evolução de caracteres morfológicos, comportamentais e ecológicos no grupo de L. pentadactylus (Anura, Leptodactylidae) - Silva, Wagner Rodrigues da (2009)
Historical Ecology unifies concepts in ecology, behavior and phylogeny. To determine the evolutionary context of reproductive characters within the Leptodactylus pentadactylus species group and also to explore questions such as predation and habitat selection, I described the reproductive ecology of two key species, L. labyrinthicus and L. syphax) (Anura, Leptodactylidae). Field observations and experiments (2004 2008) were carried out in areas of Cerrado in southeastern and central Brazil. I characterized the oviposition sites of the two species by comparing the ecological conditions of the egglaying sites with those of nearby random points. Experiments with tadpoles were also conducted to describe their diel pattern of activity, hiding behaviour and level of susceptibility to predation by free-ranging birds. I determined whether L. syphax clutches have trophic eggs (tadpole food) by quantifying the proportion of eggs/embryos in recent nests. I also tested whether tadpoles of both species could prey on eggs of heterospecific foam nests. Leptodactylus labyrinthicus (140 mm SVL) breeds in temporary or permanent pools in swamps while L. syphax (70 mm) occurs in rocky and seasonal streams. Both species lay their eggs embedded in a white foam nest built by the amplectant pair; males beat the female cloacal fluids with both legs moving from side to side. Their foam nests were found beside the water, usually in basins excavated by the adults. Both species probably do not distribute their nests randomly across the environment, but actively choose micro-habitats with particular conditions (e.g., sheltered, close to water) that may provide relative protection for eggs/nestling tadpoles against the main risks present in their breeding sites (e.g., drying, maggot s infestation). Oviposition site selection including flexible strategies on the choice of micro-habitats in response to spatial and temporal variations has been reported for several frog species. In contrast to L. labyrinthicus, the clutches of L. syphax do not have trophic eggs, because most (90%) of the eggs develop into tadpoles. In the experiments, birds (leaf-scrapers) ate all exposed tadpoles of L. labyrinthicus, but no tadpole in the treatment where they could hide. Hence, the use of diurnal shelters and nocturnal habits may protect the tadpoles from such visual predators. Tadpoles of L. labyrinthicus can prey on eggs from heterospecific foam nests, but those of L. syphax do not. If the L. pentadactylus species cluster is monophyletic, excavated basins and foam-beating in lateral motions may be possible derived traits that arose in the common ancestor of the whole group. However, large adults, carnivorous tadpoles, and trophic eggs appear to be congruent synapomorphies of a less inclusive group. Based on this possible association of derived traits, the major reproductive features (e.g., trophic eggs, tadpole morphology and behaviour) of species of the L. pentadactylus group could be inferred largely from the body size (SVL) of adults.